New Nanoporous ?-Cyclodextrin-Containing Silicas for Sorption of Heavy Metal Nitrates - L. A. Belyakova; O. M. Shvets; D. Yu. Lyashenko (Хімія, фізика та технологія поверхні)
Nanoporous b-cyclodextrin-containing silicas, which differ by functional substituents of the wide edge of attached cyclic oligosaccharide molecules, were synthesized. Formation of the supramolecular structures (supermolecules), which chemical composition depends on the nature of adsorbed cations and functional substituents in the b-cyclodextrins molecules attached to the surface of organosilicas, was proved. The interpretation of interaction peculiarities of mercury and cadmium nitrates with the synthesized b-cyclodextrin-containing silicas was given started from the theory of hard and soft acids and bases.